Vpliv sušilnega postopka na kakovost in izkoristek bukovega žaganega lesa - Straže, Aleš (Les (Ljubljana), 2017)
We estimated the quality of beech (Fagus sylvatica) sawn timber before and after the industrial normal-temperature convection kiln drying and after air drying. We analysed 42 mm thick and 2.6 m to 5 m long boards, where we measured the number and size of end- and surface cracks, and fissures close to the knots. The orientation and direction of the wood grain, the number and size of knots as well as occurrence of red-heart and twisting were also determined. We ranked the boards using these criteria before and after the end of the drying processes in accordance with the standard of the European Organization of the Sawmill industry (EOS). We found a significant effect of drying on the occurrence of drying defects, but differences between the two procedures were not confirmed. The increase in the number and size of the surface and end cracks, especially in the boards assessed to lower B- and C-classes was obvious. The latter mainly contributed to the lowering of the quality of the sawn timber after drying from the A- to B- or lower class. After the kiln and air drying 20 % and 33 % of the sawn timber quality was degraded, respectively. The presented research was part of a larger study where we followed the quality of the beech timber from the forest to the final product
Keywords: air drying; beech; bukev; drying defects; Fagus sylvatica; kakovost lesa; kiln drying; konvekcijsko komorsko sušenje; les; napake pri sušenju; sušenje na prostem; timber quality; wood